Забезпечення стабільності екологічних характеристик автомобіля, обладнаного каталітичним нейтралізатором, в умовах експлуатації - Шапко, С. В. (НТУ "ХПІ", 2015)
Розроблений метод розрахунку екологічних показників автомобіля враховує потрібні очисні властивості каталітичного нейтралізатора у разі потреби його встановлення з урахуванням вимог стандартів, на виконання яких орієнтований автомобіль. Запропонований перелік показників, за якими оцінюються зміни очисних властивостей нейтралізатора під час експлуатації автомобіля. Проведені експериментальні дослідження підтверджують запропоновані та запатентовані конструктивні рішення щодо забезпечення стабільності екологічних характеристик автомобіля з каталітичним нейтралізатором.

The method of calculation of environmental performance vehicle with a catalytic converter, the algorithms which take into account the requirements of national and international standards, planned frequency of maintenance of the vehicle, minimizing equipment costs vehicle neutralizer and its service. They can be used at the design stage of the vehicle or equipment by serial converter of the vehicle. The proposed list of indicators used to assess changes in treatment properties of the converter during operation of the vehicle. Experimental studies confirm the proposed and patented designs for stability of the ecological characteristics of a car with a catalytic converter. The desired coefficient of purification catalytic converter must consider the admissible emission standards for each component, the deterioration of ecological indicators for the period of vehicle operation between technical services, as well as the deterioration of the purification properties of the catalyst after each subsequent regeneration. Solving the problem this way, you can develop the design of the neutralizer with a minimal but sufficient amount of the catalyst for purification of exhaust gases to the level of the applicable requirements. This will reduce the cost of equipment neutralizer of the vehicle. Could be another challenge. At the equipment of the vehicle catalytic converter is determined by the stock of environmental indicators on the validity of their deterioration in operation. The value of this stock is compared with the stability and define the allowed mileage. Based on the data, is determined by the frequency of services neutralizer, which should be coordinated with the current frequency of maintenance of the vehicle.
The stability of the ecological characteristics of a vehicle equipped with a catalytic сonverter in conditions
Keywords: відпрацьовані гази; стандарти; очисні властивості; витрата палива; vehicle; catalytic converter; exhaust gases; environmental stability; characteristics